Evaluation of Safety of Lidocaine with Epinephrine In Known Hypertensive Patients Requiring Dental Surgery - Saeed, Shahrukh Ahmed; Mahmood, Saad; Rasheed, Dil; Khan, Nazir Ahmed; Ejaz, Sana; Maryam, Tehmina (Pakistan Armed Forces Medical Journal, 2025)
Objective: To demonstrate safety of changes in blood pressure and heart rate in a group of hypertensive patients following administration of 3.6 ml of a 2% lignocaine with 1: 100,000 epinephrine dental local anaesthesia.Study Design: Quasi-experimental studyPlace and Duration of Study: This study was done at 20 Military Dental Centre, CIMS Dental College, Multan, Pakistan, from Jan  to Jun 2023.Methodology: The study involved 80 patients scheduled for tooth extraction in the OMFS outpatient department. Of these, 15 had stage 1 hypertension, 15 had stage 2 hypertension, and 15 were pre-hypertensive. The Control Group included 35 normotensive patients requiring tooth extraction, matched for age and sex.Results: Out of 80 participants, 48(60.0%) were male, and the Mean age of the patients was 52.11±4.22 years. Mean of (Systolic Blood Pressure) SBP increased in all the groups after two minutes of local anesthetic injection. After five minutes, Systolic blood pressure drops off to baseline in all groups. The overall fall in SBP had a statistically significant difference before and after two and five minutes’ local anesthetic injection in all groups, as p-values < 0.05.Conclusions: Patients with stage 2 hypertension involved in this trial had a reduction in systolic blood pressure thanks to dental local anaesthetic using epinephrine. Patients with systolic blood pressure hypertension experienced a drop of 21mm Hg, however there were no negative side effects.